Hecataeus of Abdera and a New Conjecture in Josephus, Contra Apionem 1.189 - Capponi, Livia (Histos, 2011)
This paper proposes a new conjecture in a much-discussed passage of Josephus, Contra Apionem 1.189. The passage poses several problems: the precise meaning of a phrase; the historical context of the passage; and its authenticity (that is, whether it is a genuine fragment of the Greek historian Hecataeus of Abdera, as Josephus supposes, but most recent scholarly treatments do not). These problems are necessarily interconnected. The new conjecture aims to make sense of the disputed wording and of the historical context and to reaffirm basic authenticity. The passage thus emerges as containing valuable historical information about the Jewish settlement made by Ptolemy Soter; as illuminating alike Ptolemaic, Greek and Jewish traditions about the history of the Jews under the Ptolemies; and as reaffirming a basic Hecataean core for the particular material and hence the essential authenticity of the book On the Jews attributed to Hecataeus.